The complete mitochondrial genome of the gadwall (Anas strepera). Issue 2 (3rd July 2019) - Wei, Qinguo; Wu, Xiaoyang; Hu, Yanran; Sun, Guolei; Chen, Jun; Gao, Xiaodong; Sha, Weilai; Zhang, Honghai
Abstract: The gadwall Anas strepera was widely distributed migratory duck in the family of Anatidae. The complete mitochondrial genome of gadwall was sequenced in this study to explore the mitogenomic characteristics and figure out its phylogenetic relationships within Anatidae. The mitogenome is a circular DNA molecule of 16600 bp in length with 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and a control region. The overall base composition of the mitogenome was A: 28.84%, T: 22.19%, G: 16.15%, C: 32.81%. Phylogenetic analysis showed that the Anas strepera was closed to Anas platyrhynchos .